Extenuating circumstances : stories of crime and suspense - Oates, Joyce Carol, 1938- (The Mysterious Press, 2022)
"Two hitmen in a depressed rust belt town struggle with a job gone wrong. A girl witnesses a horrifying accident and carries it with her for the rest of her life. Medical students bring a severed foot to a college party. Five-time Pulitzer Prize finalist Joyce Carol Oates has made a career of exploring the forbidden corners of human experience, and the stories collected here, spanning her first three decades as a writer, are among her most unsettling and unforgettable works to date. These tales have not appeared in any form this century--until now; formally fresh and endlessly experimental, they show a writer boldly engaging with disturbing truths and terrifying possibilities, and deconstructing the tropes and expectations of traditional prose writing as she does so. But beyond their stylistic ingenuity, these are creepy, suspenseful stories that cut straight to the bone; their darkness will linger long after the final page is turned"--